Numerical Analysis of the Fractional-Order Nonlinear System of Volterra Integro-Differential Equations. (21st October 2021) - Sunthrayuth, Pongsakorn; Ullah, Roman; Khan, Adnan; Shah, Rasool; Kafle, Jeevan; Mahariq, Ibrahim; Jarad, Fahd
Abstract : This paper presents the nonlinear systems of Volterra-type fractional integro-differential equation solutions through a Chebyshev pseudospectral method. The proposed method is based on the Caputo fractional derivative. The results that we get show the accuracy and reliability of the present method. Different nonlinear systems have been solved; the solutions that we get are compared with other methods and the exact solution. Also, from the presented figures, it is easy to conclude that the CPM error converges quickly as compared to other methods. Comparing the exact solution and other techniques reveals that the Chebyshev pseudospectral method has a higher degree of accuracy and converges quickly towards the exact solution. Moreover, it is easy to implement the suggested method for solving fractional-order linear and nonlinear physical problems related to science and engineering.